LUXÍMETRO DIGITAL PARA MONITORAMENTO DOS NÍVEIS DE ILUMINÂNCIA DE INTERIORES - Bender, Vitor C.; Giacomini, Julian C.; Guisso, Ronaldo A.; Quevedo, Josemar d. O.; Danette, Evandro; Canal, Ivan P. (Salão do Conhecimento, 2013)
Resumo